The Dialectics of Santri’s Adab and Digital Distraction in Islamic Education: A Reinterpretation of Adab al-‘Ālim wa al-Muta‘allim by KH. Hasyim Asy’ari - Hidayat, Muhammad Arifandi; Marwiyah, Syarifatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the dialectical relationship between the concept of adab in classical Islamic educational tradition and the phenomenon of digital distraction in contemporary educational contexts, with particular reference to the thought of KH. Hasyim Asy’ari in Adab al-‘Ālim wa al-Muta‘allim. Employing a qualitative library research approach, the study integrates content analysis, conceptual synthesis, and dialectical analysis to explore the relevance of classical ethical frameworks in addressing modern digital challenges. The findings indicate that adab constitutes a holistic ethical system that regulates intention, behavior, and epistemic relations in the learning process, while digital distraction operates as a multidimensional phenomenon affecting cognitive, socio-emotional, and moral domains. The tension between the discipline and ethical intentionality embedded in adab and the immediacy and fragmentation of digital culture reflects a disruption of the foundational structure of meaningful learning. However, a point of convergence is identified through the concept of self-regulation, which serves as a bridge between classical Islamic ethics and modern educational psychology. Within this integrative framework, adab functions as a normative foundation, while self-regulation provides an operational mechanism for addressing digital distraction, particularly in shaping the character of santri in contemporary contexts. This study contributes to the development of an integrative and contextually grounded framework that connects classical ethical traditions with the demands of modern education.